Visual Indicator Based on Leuco Crystal Violet for Radiation Processing Technology - Shinde, Santosh Harsichandra; Mondal, Suvendu; Sathian, Vilippalil (IPTEK The Journal for Technology and Science, 2025)
One of the important technologies for food preservation and processing is radiation processing, which is growing at an ever-increasing rate in India. Efforts are being made to make it more cost-effective, so there is always a need for cost-effective, indigenously developed visual indicators for providing easy identification and segregation of irradiated products. Thus, the development of a cost-effective visual indicator based on leuco crystal violet for doses greater than or equal to ten kiloGray was undertaken. Current research work deals with fabrication and characterization of various parameters such as optimum composition, light stability, temperature effect, and effect of relative humidity on the new indicator.